Comparing the hot corrosion of (100), (210) and (110) Ni-based superalloys exposed to the mixed salt of Na2SO4-NaCl at 750 °C: Experimental study and first-principles calculation. (February 2022) - Wei, Boxin; Chen, Chunjin; Xu, Jin; Yang, Lanlan; Jia, Yixuan; Du, Yao; Guo, Mingxiao; Sun, Cheng; Wang, Zhenyao; Wang, Fuhui
Abstract: The effect of crystal orientation on the hot corrosion behaviors of Ni-based single-crystal (SC) superalloys exposed to mixtures of 90 wt% Na2 SO4 + 10 wt% NaCl at 750 °C for 200 h were studied using the "deposit recoat" method. The results showed that the mass gains of the specimens with different orientations increased in the order of (210) < (100) < (110). The (210)-oriented specimen exhibited superior hot corrosion resistance, which resulted in the lowest mass gain. First-principles calculations indicated that the origin of the orientation-dependent hot corrosion resistance was the different diffusivities of active cations in differently oriented alloys. Highlights: Hot corrosion of Ni-based SC superalloys with different orientation were studied. Corrosion components caused severe internal attacks in superalloys. Hot corrosion resistances followed the trend (100) < (110) < (210). Roles of orientation in corrosion resistance were discussed by first-principles calculations.